Code-Mixing of Language in Student's Daily Conversations at Islamic boarding school - Kirom, Abdul; Ainin, Moh; Wijaya, Mualim; Hasanah, Uswatun; Qibtiyah, Luthfatul (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This research aimed to describe the types of linguistic interference in the conversations of students at the Al-Amien Islamic boarding school Prenduan of Sumenep Madura, and to describe the linguistic methods for correcting errors in their linguistic interference. In this study, the researchers used a descriptive qualitative approach. The study relied on interviewing some professors at the institute, observation, and documentation of all data. The researchers arrived at several results, including: The types of linguistic overlap that occurred during students’ conversations in Arabic at the Al-Amien Islamic Boarding School Prenduan of Sumenep Madura were represented by morphological overlap from the Madurese language to the Arabic language, morphological overlap from the Indonesian language to the Arabic language, semantic overlap from the Madurese language to the Arabic language, and semantic overlap from the Indonesian language to the Arabic language. Al-Amien Islamic Boarding School Prenduan of Sumenep Madura employed methods for teaching the Arabic language through daily conversation expressions to rectify linguistic overlaps among students. This approach was documented in booklets authored by KH. Mohammad Marzuki Ma’ruf, who held the primary responsibility for Arabic language instruction. The booklets included: A book on correcting errors in the Language Week Arabic, a book of terminology and error correction, a book of common terms, a book of daily conversation, and a book of daily terms and methods. From these mentioned books, materials for the error correction program for linguistic interference were extracted, and activities were conducted throughout the Al-Amien Islamic Boarding School, encompassing both formal and informal activities spanning twenty-four hours.